DISKRESI DAN PERTANGGUNGJAWABAN PEMERINTAH DALAM PENYELENGGARAAN PEMERINTAHAN - Ansori, Lutfil (Jurnal Yuridis, 2015)
This paper aims to determine the limits of the use of discretion in governance and its responsibility when there is a deviation of the law. As a welfare state, the principle of legality alone is not enough to be actively involved in serving the interests of the community. This discretion emerged as an alternative to fill the shortcomings and weaknesses in the application of the principle of legality (wetmatigheid van bestuur). The use of discretionary powers by government officials can only be done in certain cases where the legislation in force does not set or because the existing regulations governing something is not clear, and it is done in an emergency / urgent in the interest of public. Bounds in the use of discretion is the General Principles of Good Governance (AUPB). While responsibility for discretionary decisions is divided into two, (1) as the responsibilities of office and (2) as a personal responsibility. As the responsibilities of office, when acting for and on behalf of the office (ambtshalve) in which there is no matter of maladministration. As a personal responsibility, if the use ofthese powers are matters of maladministration.